2022
DOI: 10.1021/acs.jpca.2c06355
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Odd- and Even-Numbered Hydrogen Cluster Cations Using the Direct Ab Initio Molecular Dynamics Approach

Abstract: The photoreaction of hydrogen clusters caused by cosmic-ray irradiations plays a crucial role in interstellar molecular clouds because the reaction of molecules takes place in these surrounding clusters. Previous gas-phase experiments introduced the reaction products after the ionization of the neutral hydrogen cluster. In the experiments, the odd-numbered hydrogen cluster cation, H+(H2) m , was the main product, while the even-numbered cluster cation, (H2) n +, was the minor product. However, the formation y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Nevertheless, a recent theoretical study using initio molecular dynamics method suggested possible forms of hydrogen clusters (or ion clusters) of ≈1–2 nm size; in which clusters, H 2 molecules and ions are loosely interconnected, rather than in a condense form. [ 33 ] More adequately, the SAXS‐revealed nanoparticles shown in Figure 7e should be regarded as hydrogen‐enriched zones, which sizes would associate with the available pore sizes of the fractal network of the SCB conjugated polymer formed in the water‐based solution, as illustrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a recent theoretical study using initio molecular dynamics method suggested possible forms of hydrogen clusters (or ion clusters) of ≈1–2 nm size; in which clusters, H 2 molecules and ions are loosely interconnected, rather than in a condense form. [ 33 ] More adequately, the SAXS‐revealed nanoparticles shown in Figure 7e should be regarded as hydrogen‐enriched zones, which sizes would associate with the available pore sizes of the fractal network of the SCB conjugated polymer formed in the water‐based solution, as illustrated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%